Detecting re-infection in patients after an initial diagnosis of gonorrhoea: is routine recall for re-screening useful?. (August 2015) - Fernando, KA; Fowler, T; Harding, J; Flew, S; Caley, M; Phattey, J; Ross, JDC
To assess the outcome of routine sexually transmitted infection re-screening after a three-month interval in unselected patients diagnosed with gonorrhoea, we sought to assess whether this active approach would result in an increase in the number of people attending clinic and subsequently diagnosed with gonorrhoea re-infection, compared with normal re-presentation rates. A recall group of patients were invited for re-screening three months after their initial diagnosis of gonorrhoea. Permission was sought to send a reminder two weeks prior to their scheduled recall appointment. Comparisons were made with a historical control group of patients with gonorrhoea in the absence of any formal recall. Of the 242 patients in the intervention arm, 96 (40%) re-attended within six months, and 15 (6%) tested gonorrhoea positive. Two hundred and two patients were assessed in the control group, of whom 45 (22%) re-attended within six months, and 13 (6%) tested gonorrhoea positive. Women were more likely than men to re-attend following active recall, but they were not at higher risk of re-attending while re-infected with gonorrhoea. Active recall following a gonorrhoea diagnosis significantly increases re-attendance rates for repeat screening but did not result in an increased number of subsequent gonorrhoea diagnoses.